The Intellectual Turn in Muhammadiyah: Organizational Dynamics during Indonesia’s Political Transition, 1990–1998 - Aslama Nada Rizal; Fauzan Syahru Ramadhan (Analisis Sejarah, 2025)
This research examines the dynamics within the management of Muhammadiyah from 1990 to 1998, focusing on the dominance of Muslim intellectual groups and the conflict between the modern or intellectual and traditional groups. This research traces the historical context chronologically and comprehensively regarding developments at the center of Muhammadiyah management and the social and political impact on Muhammadiyah organizations at the grassroots level. The research uses a historical method. This research reveals that the opportunities for Muslim intellectuals to be further involved in Muhammadiyah management had created tension between those who agreed with modernization and progressiveness and those who denied and tended to hold the old ways. The conflict had given rise to dualism in the central management of Muhammadiyah, the impact of which had occurred in several branch-level organizations.